Moisés Bertoni: ciência, família e identidade nacional do/no Paraguai (1888-1929) - Fiuza , Wagner Henrique Neres (2021)
The objective of the thesis is to analyze the narratives of/about Moisés Bertoni that involve the construction of a Paraguayan national identity. A Swiss immigrant living in Paraguay at the end of the 19th century, Bertoni sought there to build a future in which science, family and nation could converge. For this, he turned to the Guarani past, which he tried to transform into the future of Paraguay. In this process, he himself was elevated to the status of a national symbol. To understand this process, the corpus of sources includes research in/about museums, libraries, newspaper excerpts, legislative texts and biographies, as well as private and public texts signed by Moisés Bertoni, such as letters, magazine articles and books. First, we problematize how Bertoni established a narrative identity written in his family letters, in which a construction of the self against a horizon of optimistic expectations collided with a space of frustrating experiences, and produced narratives of hope, triumph, anger, fear and loneliness. Then, we analyze the insertion of Bertoni in the network of intellectuals called “nineteenth century”. Afterwards, we discussed the contradictions in his narrative about the Guarani, which sought to build a past for Paraguay. In this narrative, Bertoni sought prehistoric origins, flirted with the fantastic, created concepts, methodically revised colonial historiography and contemporary Brazilian historiography to defend the Guarani and miscegenation as a primordial element of Paraguayan nationality. Finally, we analyze the uses of memory of/about Moisés Bertoni, which went through processes of celebration, abandonment, rediscovery and capitalization. In this bulge, whether in funeral speeches or in the management of his former home as a museum, a singular Bertoni, a Guarani herald and self-sacrificing national hero, was constituted and disseminated. Therefore, the thesis argues that the idea of the Paraguayan nation was as important to constitute the author Moisés Bertoni as his authorial practice for the formation of a national identity of Paraguay, practices fed back throughout the 20th century.